Both Fidaxomicin and Vancomycin Inhibit Outgrowth of Clostridium difficile Spores - Allen, Charlotte A. (American Society for Microbiology, 2013)
Fidaxomicin (FDX) is approved to treat Clostridium difficile-associated diarrhea and is superior to vancomycin in providing a sustained clinical response (cure without recurrence in the subsequent 25 days). The mechanism(s) behind the low recurrence rate of FDX-treated patients could be multifactorial. Here, we tested effects of FDX, its metabolite OP-1118, and vancomycin on spore germination and determined that none affected the initiation of spore germination but all inhibited outgrowth of vegetative cells from germinated spores.